Anti-bacterial efficacy of alcoholic hand rubs in the Kenyan market, 2015. Issue 1 (December 2017) - Ochwoto, Missiani; Muita, Lucy; Talaam, Keith; Wanjala, Cecilia; Ogeto, Frank; Wachira, Faith; Osman, Saida; Kimotho, James; Ndegwa, Linus
Abstract Background Hand hygiene is known to be effective in preventing hospital and community-acquired infections. The increasing number of hand sanitizer brands in Kenyan hospitals and consumer outlets is of concern. Thus the main aim of this study was to evaluate the anti-bacterial efficacy and organoleptic properties of these hand sanitizers in Kenya. Methods This was an experimental, laboratory-based study of 14 different brands of hand sanitizers (coded HS1-14) available in various retail outlets and hospitals in Kenya. Efficacy was evaluated using standard non-pathogenicEscherichia coli (ATCC 25922), Staphylococcus aureus (ATCC 25923) andPseudomonas aeruginosa (ATCC 27853) as per the European Standard (EN). The logarithmic reduction factors (RF) were assessed at baseline and after treatment, and log reduction then calculated. Ten and 25 healthy volunteers participated in the efficacy and organoleptic studies respectively. Results Four (28.6%) hand sanitizers (HS12, HS9, HS13 and HS14) showed a 5.9 reduction factor on all the three bacteria strains. Seven (50%) hand sanitizers had efficacies of <3 against all the three bacteria strains used. Efficacy on E. Coli was higher compared to the other pathogens. Three hand sanitizers were efficacious on one of the pathogens and not the other. In terms of organoleptic properties, gel-based formulations were rated far higher than the liquid based formulations brands. Conclusion Fifty percent (50%) of the selected hand sanitizers in the Kenyan market have efficacy that falls below the World Health Organization (WHO) and DIN EN 1500:2013. Of the 14 hand sanitizers found in the Kenyan market, only four showed efficacies that were comparable to the WHO-formulation. There is a need to evaluate how many of these products with <3 efficacy that have been incorporated into the health system for hand hygiene and the country's policy on regulations on their usage.